Strategi Digital Marketing Syariah dalam Meningkatkan Loyalitas Wisatawan pada Destinasi Halal Tourism - Ananda Rauf Nurhidayah Isnaini (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2025)
The development of digital technology has encouraged the implementation of sharia digital marketing strategies in the halal tourism industry. This study aims to analyze the role of sharia digital marketing in increasing tourist loyalty toward halal tourism destinations through a library research approach. This research employed a qualitative method with a literature study design by collecting data from scientific articles, national and international journals, and other relevant academic sources indexed in Scopus, Web of Science, and Google Scholar. Data were analyzed using descriptive analysis and narrative synthesis to identify research trends, conceptual relationships, and research gaps related to halal tourism and tourist loyalty. The findings indicate that sharia digital marketing implemented through social media, Islamic e-branding, halal content, digital engagement, and transparent halal communication contributes to building tourist trust, strengthening destination image, increasing perceived value, and encouraging tourist satisfaction and electronic word of mouth (e-WOM), which subsequently influence tourist loyalty. The study also highlights that the effectiveness of sharia digital marketing depends not only on digital promotion intensity but also on the consistency between halal promotion and the quality of halal tourism services